Critiquing Anthropocentrism in Henry Ole Kulet’s Vanishing Herds - Jaishi, Pushpa Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
Vanishing Herds (2011) is Henry Ole Kulet’s novel that hovers around the ecological depletion caused by the anthropocentric attitude of the human beings. Set in the East African Savannah, the novel grapples with the critical issue of anthropogenic environmental degradation. The novel is based on the tribulations of a young Maasai couple –Kedoki and Norpisia whose epic journey through the wilderness provides a window through which the destruction of the physical environment can be viewed. Additionally, the text catalogues the challenges faced by a pastoralist community’s attempt to come to terms with the socio-economic realities of a fast-evolving contemporary society. The paper is an attempt to study this novel under the surveillance of green lens and throw light on the ecological destruction especially the clearing of the forest by human self centered endeavors and to critique the anthropocentric attitude of the human beings that render the environment at the verge of destruction.